Impact of Marketing Mix and Brand Religiosity Aura on Consumer Purchase Decisions: A Study of Rabbani Muslim Fashion - Reny Fitriana Kaban; Prameswara Samofa Nadya; Maulana Ilham Akbar (Journal of Business, Finance, and Banking, 2026)
Muslim fashion has emerged as a significant segment within the global halal economy, yet empirical studies examining the interplay between conventional marketing strategies and religion-based brand identity in driving consumer purchase behavior remain limited. This study investigates the influence of the marketing mix comprising product, price, place, and promotion alongside brand religiosity aura on consumer purchase decisions within the context of Rabbani, an established Indonesian Muslim fashion brand. Employing a quantitative cross-sectional design, data were collected from 100 purposively selected consumers with prior purchasing experience of Rabbani products. The findings reveal that all five variables exert statistically significant effects on purchase decisions, with place and promotion emerging as the dominant predictors. These results underscore the strategic importance of distribution accessibility and promotional communication in shaping consumer behavior within the Muslim fashion market, while also highlighting the role of religious brand identity as a distinct purchase driver beyond conventional marketing attributes. This study contributes to the growing literature on Islamic marketing and halal consumption by providing empirical evidence from an emerging market context. Future research is encouraged to broaden geographical sampling and to incorporate contemporary variables such as social media influence, digital marketing engagement, and generational consumption patterns, particularly among Generation Z Muslim consumers